2002
DOI: 10.1093/jexbot/53.371.1187
|View full text |Cite
|
Sign up to set email alerts
|

Determining critical pre‐ and post‐anthesis periods and physiological processes in Lycopersicon esculentum Mill. exposed to moderately elevated temperatures

Abstract: To determine the thermosensitive periods and physiological processes in tomato flowers exposed to moderately elevated temperatures, tomato plants (Lycopersicon esculentum Mill., cv. NC 8288) were grown at 28/22 degrees C or 32/26 degrees C day/night temperature regimes and then transferred to the opposite regime for 0-15 d before or 0-24 h after anthesis. For plants initially grown at 28/22 degrees C, moderate temperature stress before anthesis decreased the percentage of fruit set per plant, but did not clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
163
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 31 publications
10
163
0
2
Order By: Relevance
“…Jagadish et al, 2007;Mamun et al, 2006;Prasad et al, 2006), relating chilling and heat stress during booting (early gametophyte development) and flowering to higher spikelet sterility. Similarly, the effect of high temperatures during flowering in tomato (Solanum lycopersicum L.) has also been studied in detail, and not only extreme high temperatures, but even a mild increase in temperature during a short spell coincident with some flowering stages have been shown to affect negatively fruit set Page 6 of 24 A c c e p t e d M a n u s c r i p t 6 (Abdulbaki and Stommel, 1995;Sato et al, 2002). Bell pepper (Capsicum annum L.) has been reported to be equally sensitive to high temperature stress during flowering (Erickson and Markhart, 2002).…”
Section: Page 5 Of 24mentioning
confidence: 99%
See 2 more Smart Citations
“…Jagadish et al, 2007;Mamun et al, 2006;Prasad et al, 2006), relating chilling and heat stress during booting (early gametophyte development) and flowering to higher spikelet sterility. Similarly, the effect of high temperatures during flowering in tomato (Solanum lycopersicum L.) has also been studied in detail, and not only extreme high temperatures, but even a mild increase in temperature during a short spell coincident with some flowering stages have been shown to affect negatively fruit set Page 6 of 24 A c c e p t e d M a n u s c r i p t 6 (Abdulbaki and Stommel, 1995;Sato et al, 2002). Bell pepper (Capsicum annum L.) has been reported to be equally sensitive to high temperature stress during flowering (Erickson and Markhart, 2002).…”
Section: Page 5 Of 24mentioning
confidence: 99%
“…Tapetum -the innermost layer of the anther wall-hypertrophy in rice (Nishiyama, 1984) and its earlier degeneration in many other species (Ahmed et al, 1992;Erickson and Markhart, 2002;Porch and Jahn, 2001), which deprives developing pollen grains from essential nutrients and metabolites, is another symptom frequently reported as accompanying pollen sterility under low and high temperature stresses. However, development of the external layers of the anther wall, such as epidermis, endothecium, stomium and septum, has also been shown to be disrupted (Ahmed et al, 1992;Matsui and Omasa, 2002;Porch and Jahn, 2001;Sato et al, 2002), finally affecting anther dehiscence and leading to male sterility even though the pollen is viable. Major alterations in gene expression under high temperature stress have been shown, paralleling tapetum degeneration and pollen sterility, in barley (Hordeum vulgare L.) (Abiko et al, 2005) and rice (Endo et al, 2009).…”
Section: Male Development: Pollen Development and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences observed in this study with respect to sowing date are consistent with the work of Sisodia and Mcginnis (1970), D Guerra et al who found varying levels of meiotic instability in triticale genotypes sown at different dates. According to Sato et al (2002), in many species the reproductive stage is more sensitive to abiotic stresses than the vegetative stage. Saini et al (1997) considered the meiotic stage as the most sensitive period in the life cycle of seed plants.…”
Section: Meiotic Behaviormentioning
confidence: 99%
“…Besides maize, many other cereals, such as wheat (Triticum aestivum), barley (Hordeum vulgare), and rice (Oryza sativa), are affected by high temperatures during the reproductive phase (Barnabás et al, 2008). Negative effects of heat stress have also been reported for other important crops from various plant families, such as tomato (Solanum lycopersicum) (Sato et al, 2002(Sato et al, , 2006 and pepper (Capsicum annuum) (Marcelis et al, 2004) from the Solanaceae family, canola and mustard (Brassica juncea, Brassica rapa, and Brassica napus) (Angadi et al, 2000;Gan et al, 2004) from the Brassicaceae family, soybean (Glycine max) (Djanaguiraman et al, 2013) and chickpea (Cicer arietinum) (Clarke and Siddique, 2004) from the Fabiaceae family, and peach (Prunus persica) (Hedhly et al, 2005) and cherry (Prunus avium) (Hedhly et al, 2004) from the Rosaceae family. Thus, heat stress is an important factor that affects crop yields worldwide.…”
Section: Introductionmentioning
confidence: 99%